Data to: Determination of polyoxymethylene (POM) water partition coefficients for DDT and its degradation products, with interlaboratory comparison of the passive sampling methodology and bioaccumulation in earthworm (Eisenia fetida) - Enell, Anja; Casey, Stephanie; Au Musse, Ayan; Josefsson, Sarah; Kikuchi-McIntosh, Johannes; Nilén, Greta; Wiberg, Karin; Dahlberg, Anna-Karin; Larsson, Maria (Swedish Geotechnical Institute, 2025)
The dataset contains results from:
1) shake tests to determine partition coefficients of ten organochlorine compounds, DDX, (DDT and degradation products of DDT) between polyoxymethylene (POM) and water, KPOM. The batch tests were performed in 100 mL glass bottles, on 76 μm thick POM strips (4 × 5 cm) shaken with 100 g MilliQ water, containing 1 g/L NaN3 and 10 mmol/L PO4 buffer solution, spiked with four DDX concentration levels, C1, C2, C3 and C4, with pH adjusted to H 4.1, 7.0 or 8.4. The concentration of DDX in the POM and in the water phase was analysed after 3, 7, 14, 28 or 56 days of shaking.
2) Characterisation of soil samples from nine DDX-contaminated forest plant nurseries in Sweden. The characterisation includes analysis of DDX concentrations (by two laboratories Lab A and Lab B), texture, pH, carbon and nitrogen content, inorganic contaminants, other organic pesticides, water holding capacity, and POM analysis (performed by Lab A and Lab B). The POM analyses were performed using 76 μm thick POM strips (4 × 5 cm) placed in glass bottles together with 25 g of homogenised soil (calculated as dry weight) and then mixed with 93 ml of water containing CaCl2 and NaN3. The bottles were tumbled for 28 days in the dark. The DDX concentration in the POM strips was then analysed. In order to study variance caused by differences in the extraction and analysis steps in the two laboratories and thereby exclude any other variance (e.g. caused by heterogeneous contaminant distribution in the soil samples and differences in the implementation of the shaking experiment), six of the POM strips in each laboratory were cut into halves (‘I’ and ‘II’) after terminating the tumbling (24 halves in total). ‘The ‘I’ halves (n=12) were then extracted and analysed by Lab B while Lab A extracted and analysed the ‘II’ halves (n=12).
3) Ecotoxicity test on the nine soil samples with Eisenia fetida ISO 11268-1:2012 (mortality and growth (adult biomass) after 28 days of exposure) and ISO 11268-2:2023 (reproduction after 56 days of exposure) and DDX concentrations in earthworms, Cworm in wet weight, (ng/gww) and worm lipid content after 28 days of exposure.

The data form the basis of the study/article: Determination of polyoxymethylene (POM) water partition coefficients for DDT and its degradation products, with interlaboratory comparison of the passive sampling methodology and bioaccumulation in earthworm (Eisenia fetida). Detailed description of the analytical methods used are described therein, as well as in the Supporting Material to the article.

Datasetet innehåller resultat från:
1) skaktester för att bestämma fördelningskoefficienter för tio organiska klorföreningar, DDX, (DDT och nedbrytningsprodukter till DDT) mellan polyoximetylen (POM) och vatten, KPOM. Skaktesterna utfördes i 100 mL glasflaskor, på 76 μm tjocka POM-remsor (4 × 5 cm) som skakades med 100 g MilliQ-vatten, innehållandes 1 g/L NaN3 och 10 mmol/L PO4-buffertlösning, spikad med fyra DDX-koncentrationsnivåer, C1, C2, C3 och C4, där pH justerats till H 4,1, 7,0 eller 8,4. Koncentrationen av DDX i POM och i vattenfasen analyserades efter 3, 7, 14, 28 eller 56 dagars skakning.
2) Karakterisering av jordprover från nio plantskolor i Sverige som är förorenade av DDX. Karakteriseringen omfattar analys av DDX-koncentrationer (av två laboratorium Lab A och Lab B), textur, pH, kol- och kväve-innehåll, oorganiska föroreningar, andra organiska bekämpningsmedel, vattenhållande förmåga, samt POM-analys (utförd av Lab A och Lab B). POM-analyserna utfördes med 76 μm tjocka POM-remsor (4 × 5 cm) som lades i glasflaskor tillsammans med 25 g homogeniserad jord (beräknad som torrvikt) och blandades sedan med 93 ml vatten som innehöll CaCl2 och NaN3. Flaskorna vändes i vändapparat i 28 dagar i mörker. Därefter analyserades DDX koncentrationen i POM-remsorna. För att studera varians orsakad av skillnader i extraktions- och analysstegen i de två laboratorierna och därigenom utesluta all annan varians (t.ex. orsakad av heterogen föroreningsspridning i jordproverna och skillnader i genomförandet av skakförsöket), delades sex av POM-remsorna i varje laboratorium i halvor (”I” och ”II”) efter skakförsöket (totalt 24 halvor). ”I"-halvorna (n=12) extraherades och analyserades sedan av Lab B medan Lab A extraherade och analyserade ’II’-halvorna (n=12).
3) Ekotoxicitetstest med Eisenia fetida ISO 11268-1:2012 (dödlighet och tillväxt (vuxen biomassa) efter 28 dagars exponering) och ISO 11268-2:2023 (reproduktion efter 56 dagars exponering) samt DDX koncentrationer i daggmask, Cworm i våtvikt, (ng/gww) och maskarnas lipidinnehåll efter 28 dagars exponering.

Datan ligger till grund för studien/artikeln: Determination of polyoxymethylene (POM) water partition coefficients for DDT and its degradation products, with interlaboratory comparison of the passive sampling methodology and bioaccumulation in earthworm (Eisenia fetida). Utförlig beskrivning av analysmetoderna som använts finns beskrivna där i, samt i Supporting Material till artikeln.
Data för artikeln: Determination of polyoxymethylene (POM) water partition coefficients for DDT and its degradation products, with interlaboratory comparison of the passive sampling methodology and bioaccumulation in earthworm (Eisenia fetida)
Keywords: ECOTOXICOLOGY; BIOAVAILABILITY; DDT; DDT; bio-availability; biotillgänglighet; ecotoxicology; ekotoxikologi; Environmental Sciences; Miljövetenskap